BIOINFORMATICS TOOLS: ESSENTIAL FOR THE DEVELOPMENT AND DISCOVERY OF MEDICINES - Srivastava, Vivek; Kumar, Ajay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Pharmaceutical research and development is a difficult, high-risk, time-consuming, and potentially lucrative process. Pharmaceutical corporations invest millions of dollars to get a medicine to market. A novel medication demands technical competence, human resources, and a large capital commitment. It also requires stringent adherence to laws on testing and manufacturing standards before a new medicine may be used in the general public; in fact, some drugs fail to enter the market. All of these considerations simply raise the expense of researching and developing a novel chemical entity. Bioinformatics/Tools in the drug design process has a favorable impact on the whole process and may speed up different processes of drug design while lowering costs and total time. The current note focuses on bioinformatics' importance in the drug development and research method.